Pemetaan Lahan Kritis di Kabupaten Dharmasraya Menggunakan Sistem Informasi Geografis - Gita Sofia; Afrital Rezki; Yuherman Yuherman (Journal on Education, 2023)
This research is motivated by several problems, namely the distribution of critical land in Dharmasraya Regency and the condition of critical land in Dharmasraya Regency. And the purpose of this research is to know and analyze the distribution of critical land in Dharmasraya district and the condition of critical land in Dharmasraya district. The type of research used in this research is the Quantitative Approach Method. The population in this study were 11 districts in Dharmasraya district. Sampling in this study using Total Sampling. The results of this study can be concluded that The distribution of very critical land classes is only spread in the Asam Jujuhan District, which is 0.1 Ha. The critical land class in the Asam Jujuhan District is the most extensive, namely 606 ha. The widest class of potentially critical land is in the District of Koto Besar, namely 50594.6 ha, while the class of sufficiently critical land is in the District of Koto Besar with an area of ​​3315.8 ha and in the District of Asam Jujuhan with an area of ​​2349.3 ha. And the widest non-critical land class is spread over the Nine Koto sub-district with an area of ​​6,926.3 Ha. Critical land conditions in Dharmasraya Regency which have been analyzed are Very Critical of 0.1 ha, Critical Land of 2,393.4 ha (1%), Fairly Critical Land of 18,487 ha (28%), Potentially Critical Land of 258,346.2 ha (86%) and non-critical land area of ​​21321.7 ha (7%)